Body mass index and airway hyper-responsiveness in individuals without respiratory disease - Machado, D (2012)
BACKGROUND: Overweight and obesity are major health issues in Western societies. They are related with a higher risk of different co-morbidities but their relationship with airway hyperresponsiveness (AHR) is still under discussion. Nevertheless, they are related to higher severity in asthma and other respiratory diseases. The aim of the study was to analyze the AHR in individuals with normal lung function without respiratory disorders, according to body mass index (BMI) calculation. METHODS: We performed clinical observation and basal lung function tests (LFT) in 595 consecutive individuals in order to exclude respiratory disease. 377 individuals fulfilled the criteria of normal values according international guidelines. They were submitted to standardized treadmill exercise test followed by bronchodilator test. FVC, FEV1, FEF 25/75, RV and Raw were obtained at different conditions according to BMI groups (I: lean; II: normal; III: overweight; IV obese). RESULTS: 55.2% of the sample was overweight or obese, and a signficant relationship was found with female gender and older ages (p=0.0046 and p<0.0001 respectively). The positive response to exercise test or bronchodilator beta2 agonists was not significantly frequent compared with the other groups. In obese individuals the exercise markedly reduced basal Raw and increased FEF 25/75. Lean individuals showed higher basal values of RV that was reduced upon exercise. Response to 12 agonists showed no differences according to weight biotypes. CONCLUSION: BMI hampers lung function in normal individuals, and seems not to be related to AHR. Regular exercise should be encouraged in overweight and obese individuals, since it increases their bronchial permeability as shown in lower frequency of positive exercise tests. The same is advisable for lean individuals for different reasons. Their increased basal RV and Raw improve upon exercise. Despite overweight and obesity are being related to a low-grade of basal systemic inflammation, there was no association with a higher basal bronchial hyperresponsiveness in these individuals.